Antifungal and Antioxidant Activities of Pyrrolidone Thiosemicarbazone Complexes - Ahmed A. Al-Amiery; Abdul Amir H. Kadhum; Abu Bakar Mohamad (Bioinorganic Chemistry and Applications)
Metal complexes of (Z)-2-(pyrrolidin-2-ylidene)hydrazinecarbothioamide (L) with Cu(II), Co(II), and Ni(II) chlorides were tested against selected types of fungi and were found to have significant antifungal activities. The free-radical-scavenging ability of the metal complexes was determined by their interaction with the stable free radical 2,2′′-diphenyl-1-picrylhydrazyl, and all the compounds showed encouraging antioxidant activities. DFT calculations of the Cu complex were performed using molecular structures with optimized geometries. Molecular orbital calculations provide a detailed description of the orbitals, including spatial characteristics, nodal patterns, and the contributions of individual atoms.